Unexpected Importance of Potential Parasites in the Composition of the Freshwater Small-Eukaryote Community - Lepère, Cécile (American Society for Microbiology (ASM), 2008)
The diversity of small eukaryotes (0.2 to 5 μm) in a mesotrophic lake (Lake Bourget) was investigated using 18S rRNA gene library construction and fluorescent in situ hybridization coupled with tyramide signal amplification (TSA-FISH). Samples collected from the epilimnion on two dates were used to extend a data set previously obtained using similar approaches for lakes with a range of trophic types. A high level of diversity was recorded for this system with intermediate trophic status, and the main sequences from Lake Bourget were affiliated with ciliates (maximum, 19% of the operational taxonomic units [OTUs]), cryptophytes (33%), stramenopiles (13.2%), and cercozoa (9%). Although the comparison of TSA-FISH results and clone libraries suggested that the level of Chlorophyceae may have been underestimated using PCR with 18S rRNA primers, heterotrophic organisms dominated the small-eukaryote assemblage. We found that a large fraction of the sequences belonged to potential parasites of freshwater phytoplankton, including sequences affiliated with fungi and Perkinsozoa. On average, these sequences represented 30% of the OTUs (40% of the clones) obtained for each of two dates for Lake Bourget. Our results provide information on lacustrine small-eukaryote diversity and structure, adding to the phylogenetic data available for lakes with various trophic types.